PENGEMBANGAN BAHAN AJAR GEOMETRI BERBASIS ETNOMATEMATIKA BUDAYA BETAWI SEBAGAI UPAYA KONTEKSTUALISASI PEMBELAJARAN - Sholihah, Afifah; Dwirahayu, Gelar; Atiqoh, Khamida Siti Nur (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2024)
AbstractEthnomathematics is defined as the integration between a specific culture and mathematics. This research aims to develop teaching materials as a learning module on geometry building space integrated with Betawi culture. The research method is R&D with the Plomp model, which consists of five phases: preliminary investigation; design; construction/ realization; test, evaluation, and revision; also implementation. The subjects in this study consisted of three Lecturers of Mathematics Education at UIN Syarif Hidayatullah Jakarta, one junior high school teacher, and two high school teachers in the North Jakarta area. In addition, in this study, four junior high school students and four high school students were also involved as respondents in assessing the readability of the modules made.The results of assessments from experts show that the modules made are very feasible. The results of the students' responses to the learning module are included in the perfect category. So, it was concluded that the module could be used as additional material for teachers in teaching the geometry of flat buildings and building spaces using Betawi culture. Abstrak Etnomatematika merupakan integrasi antara budaya tertentu dengan matematika. Penelitian ini bertujuan untuk mengembangkan bahan ajar berupa modul pembelajaran geometri bangun ruang yang diintegrasikan dengan kebudayaan Betawi. Metode penelitiannya yaitu R&D dengan model Plomp yang terdiri dari lima fase, yaitu fase investigasi awal; desain; konstruksi/ realisasi; tes, evaluasi, dan revisi; serta implementasi. Subjek dalam penelitian ini terdiri dari tiga Dosen Pendidikan Matematika UIN Syarif Hidayatullah Jakarta, satu orang guru SMP, dan dua guru SMA di wilayah Jakarta Utara. Selain itu, dalam penelitian ini dilibatkan juga empat orang siswa SMP dan empat orang siswa SMA sebagai responden dalam menilai keterbacaan modul yang telah dibuat. Berdasarkan hasil penilaian dari ahli menunjukkan bahwa modul yang dibuat sangat layak. Adapun hasil respon peserta didik terhadap modul pembelajaran termasuk dalam kategori sangat baik. Sehingga disimpulkan bahwa modul yang dibuat dapat dijadikan sebagai bahan tambahan bagi guru dalam mengajarkan geometri bangun datar dan bangun ruang dengan menggunakan budaya betawi.